Compounds, compositions and polymer films
Patent Information
- Application Number
- CN202180066357.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-09-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2041-09-27
Smart Images

Figure CN116322951B_ABST
Abstract
Description
[0001] This invention relates to compositions suitable for preparing polymer membranes, polymer membranes, cation exchange membranes, bipolar membranes, and their preparation and use.
[0002] Ion exchange membranes are used in electrodialysis, reverse electrodialysis, electrolysis, diffusion dialysis, and many other processes. Typically, ion transport across the membrane occurs under the influence of driving forces, such as ion concentration gradients or potential gradients.
[0003] Ion exchange membranes are typically classified into cation exchange membranes and anion exchange membranes based on their primary charge. Cation exchange membranes contain negatively charged groups that allow cations to pass through but repel anions, while anion exchange membranes contain positively charged groups that allow anions to pass through but repel cations. Bipolar membranes have both a cation layer and an anion layer.
[0004] Some ion exchange membranes and bipolar membranes contain porous supports that provide mechanical strength. Because of the presence of ionicly charged polymers that separate ions with opposite charges and porous supports that provide mechanical strength, these membranes are often referred to as "composite membranes".
[0005] Cation exchange membranes can be used to treat aqueous solutions and other polar liquids, and can also be used to generate electricity.
[0006] Bipolar membranes can be used to produce acids and bases from salt solutions, such as for the recovery of hydrofluoric acid and nitric acid, for the separation and treatment of organic acids such as lactic acid and citric acid, and for the production of amino acids.
[0007] Electrical energy can be generated using reverse electrodialysis (RED), in which standard ion exchange membranes or bipolar membranes can be used. Cation exchange membranes can also be used to produce hydrogen, for example, in fuel cells and batteries.
[0008] Bipolar membranes can be prepared by many different methods. In U.S. Patent Nos. 4,024,043 and 4,057,481 (both by Dege et al.), a monolayer bipolar membrane is prepared from a pre-swollen membrane containing a relatively large amount of insoluble crosslinked aromatic polymer, on which highly dissociable cation exchange groups are chemically bonded to the aromatic nuclei to the desired depth of the membrane from only one side; subsequently, highly dissociable anion exchange groups are chemically bonded to the unreacted aromatic nuclei on the other side of the membrane.
[0009] In Japanese Patent Publications Nos. 78-158638 and 79-7196 (both Tokuyama Soda Co. Ltd.), a bipolar membrane is prepared by the following process: partially covering the membrane with a cover film, sulfonating the surface of the membrane that is not in contact with the cover film to introduce cation exchange groups, peeling off the cover film and introducing anion exchange groups on the peeled surface.
[0010] Bipolar membranes are also prepared by combining anion exchange membranes or films with cation exchange membranes or films. Two unipolar membranes with opposite selectivity can be fused together by heating and pressurization to form a bipolar membrane. For example, see Kollsman’s U.S. Patent No. 3,372,101, in which separate cation and anion membranes are combined in a hydraulic press at 150°C and a pressure of 400 Ib / sq.inch to form a bilayer bipolar membrane structure.
[0011] However, bipolar films formed in this way suffer from the drawback of high resistance resulting from their fusion. Furthermore, these films are prone to bubbling or forming water bubbles, and they can only operate for short periods at relatively low current densities.
[0012] The aforementioned drawbacks make known bipolar membranes unattractive for commercial electrodialysis operations. A bipolar membrane with good permeation selectivity and low resistivity is required.
[0013] According to a first aspect of the invention, a polymer film is provided, which can be obtained by curing a composition comprising a compound of formula (I):
[0014]
[0015] in:
[0016] R' is vinyl, epoxy, or C. 1-3 alkylene mercapto:
[0017] The value of n is 1 or 2;
[0018] The value of m is 1, 2, or 3;
[0019] M' + It is a cation;
[0020] in:
[0021] (i) When both m and n are 1, X is a vinylphenyl or formula (II):
[0022]
[0023] In equation (II):
[0024] "R" represents vinyl, epoxy, or C. 1-3 alkylene mercapto;
[0025] M” + It is a cation; and
[0026] In equation (II), the value of n is 1 or 2;
[0027] (ii) When the value of m is 2 or 3, then X is C.1-6 Alkylene, -C 6-18 Aryl or N(R”') (3-m) Each R”' is independently H or C 1-4 Alkyl; and
[0028] (iii) When the value of m is 1 and the value of n shown in equation (I) is 2, then X is equation (II) (as defined above) or C. 1-6 Alkyl, C 6-18 Aryl or N(R”')2, where each R”' is independently H or C. 1-4 alkyl;
[0029] The molar fraction of compound (I) relative to all curable compounds in the composition is greater than 0.25. In this document (including its claims), the verb "comprising" and its variations are used in their non-limiting sense to mean including items following the word, but not excluding items not specifically mentioned. Furthermore, the element referred to by the indefinite article "a" or "an" does not exclude the possibility of more than one element, unless the context clearly requires exactly one element. Therefore, the indefinite article "a" or "an" generally means "at least one". The composition of the second aspect of the invention is generally referred to as a "CEL composition".
[0030] The vinyl group has the formula –CH=CH2.
[0031] The epoxy group has the formula -C2H3O.
[0032] C 1-3 The alkylene mercapto group is of formula -C 1-3 Alkylene-SH.
[0033] M' + H is preferred + Li + Na + K + or NL4 + Each L is independently H or C 1-3 alkyl.
[0034] M” + H is preferred + Li + Na + K + or NL4 + Each L is independently H or C 1-3 alkyl.
[0035] Preferred C 6-18 The arylene groups include phenylene (C6H4) and naphthylene (C6H4). 10The H6 group can be optionally substituted.
[0036] Preferred C 6-18 Aryl groups include phenyl (C6H5) and naphthyl (C6H5) groups. 10 The H7 group can be optionally substituted.
[0037] In a preferred embodiment, n is 1 and m is 2. In this embodiment, R' and R” are preferably vinyl.
[0038] The preferred vinylphenyl group is of the formula –C6H4-CH=CH2.
[0039] The composition typically contains a compound of formula (I) and other ingredients.
[0040] M' is particularly preferred. + and M' + It is Li + This is because it results in the compound having particularly good solubility in water and aqueous liquids.
[0041] Illustrative synthetic methods for compounds of formula (I) above can be found in the Examples section below. Furthermore, many compounds of formula (I) can be prepared by methods including the following steps:
[0042] (i) Provide benzenesulfonyl chloride compounds;
[0043] (ii) React the sulfonyl chloride group of component (i) with a compound containing a sulfonamide group to obtain the compound of formula (I);
[0044] At least one of components (i) and (ii) contains a vinyl group, an epoxy group, or a thiol group.
[0045] Typically, a vinyl group, an epoxy group, or a thiol group is attached to the benzene ring of one of components (i) and (ii). In a preferred embodiment, the benzenesulfonyl chloride compound used in the method comprises one or more vinyl groups, more preferably one or two vinyl groups.
[0046] In one embodiment, the composition further comprises one and only one polymerizable group and bis(sulfonyl)imide (-SO2-N). - Compounds with the -SO2-) group.
[0047] According to a second aspect of the present invention, a composition comprising the following components is provided:
[0048] (a) Compounds of formula (I) as defined with respect to the first aspect of the invention;
[0049] Option (b) is a compound containing one and only one polymerizable group;
[0050] Optional (c) solvent; and
[0051] Optional (d) radical initiators;
[0052] Wherein, the molar fraction of the compound of component (a) relative to all curable components of the composition is greater than 0.25.
[0053] Preferably, the composition comprises one, two, or all three of components (b), (c), and (d).
[0054] Preferably, the composition of the second aspect of the present invention comprises:
[0055] (a) 20 to 80% by weight of component (a);
[0056] (b) 0 to 50% by weight of component (b);
[0057] (c) 10 to 50% by weight of component (c); and
[0058] (d) 0 to 10% by weight of the component (d);
[0059] Wherein, the molar fraction of the compound of component (a) relative to all curable components of the composition is greater than 0.25.
[0060] The preferred embodiment of the compound of formula (I) used in the composition is as described above with respect to the first aspect of the invention.
[0061] Preferably, in some embodiments, the composition comprises 30 to 75% by weight, more preferably 40 to 70% by weight of component (a).
[0062] Preferably, the molar fraction of component (a) of the composition relative to all curable components of the composition is at least 0.30, more preferably at least 0.40, and particularly at least 0.50.
[0063] Component (b) can be obtained by commercial or generally known methods.
[0064] Preferably, component (b) comprises an anionic group. Preferably, component (b) comprises disulfonamide (-SO2-N). - -SO2-) group.
[0065] Preferably, the composition comprises 0 to 40% by weight, most preferably 5 to 30% by weight of component (b).
[0066] Preferred polymerizable groups that may be present in component (b) include olefinically unsaturated groups, particularly (meth)acrylic acid groups and / or vinyl groups (e.g., vinyl ether groups, aromatic vinyl compounds, N-vinyl compounds and allyl groups).
[0067] Examples of suitable (meth)acrylic acid groups include acrylate (H2C=CHCO-) groups, acrylamide (H2C=CHCONH-) groups, methacrylate (H2C=C(CH3)CO-) groups, and methacrylamide (H2C=C(CH3)CONH-) groups. Acrylic acid groups are preferred over methacrylic acid groups because they are more reactive.
[0068] Preferred olefinic unsaturated groups are free of ester groups, as this improves the stability and pH tolerance of the resulting composition. Olefinic unsaturated groups free of ester groups include vinyl groups.
[0069] As a preferred example of a polymerizable group, a group with the following formula may be mentioned:
[0070]
[0071] Preferred olefinic unsaturated groups that may be present in component (b) are vinyl groups, for example, in the form of (meth)acrylic, allyl, or styrene groups. Styrene groups are preferred over (meth)acrylic groups because they improve the pH stability of the membrane to a range of 0 to 14, which is particularly significant for bipolar and cation exchange membranes in fuel cells.
[0072] Examples of compounds having only one olefinic unsaturated group that can be used as component (b) include the following compounds of formula (MB-α), (AM-B), and formula (III):
[0073]
[0074] In equation (MB-α),
[0075] R A2 Indicates a hydrogen atom or an alkyl group.
[0076] R A4 This refers to an organic group that contains a sulfonyl group in the form of a free acid or salt and does not have an olefinic unsaturated group; and
[0077] Z 2 It is represented as –NRa–, where Ra represents a hydrogen atom or an alkyl group, preferably a hydrogen atom.
[0078] Examples of formula (MB-α) include:
[0079]
[0080] Synthetic methods can be found, for example, in US2015 / 0353696.
[0081]
[0082] Synthetic methods can be found, for example, in US2016 / 0369017.
[0083]
[0084] In equation (AM-B),
[0085] LL 2 It represents a single bond or a divalent linker; and A represents a sulfonyl group in the form of a free acid or salt; and m represents 1 or 2.
[0086] Examples of formula (AM-B) include:
[0087]
[0088] These compounds are commercially available from companies such as Tosoh Chemicals and Sigma-Aldrich.
[0089]
[0090] in
[0091] R is a C1-C4 alkyl group, NH2, or C6-C. 12 Aryl; and
[0092] M + It is H + Li + Na + K + NL4 + , where L is H or C1-C3 alkyl.
[0093] Examples of equation (III) include:
[0094]
[0095] The synthesis methods of the four compounds with the MM prefix described above are described in the Examples section below.
[0096] Preferably, component (b) is selected from compounds of formula (AM-B) and / or formula (III), as this can give the membrane particularly good stability in a pH range of 0 to 14.
[0097] Preferably, component (c) is an inert solvent. In other words, preferably, component (c) does not react with any other component of the curable composition. In one embodiment, the solvent preferably comprises water and optionally an organic solvent, particularly wherein some or all of the organic solvent is water-miscible. Water can be used to dissolve component (a) and possibly also component (b), and the organic solvent can be used to dissolve any other organic components present in the composition.
[0098] Component (c) can be used to reduce the viscosity and / or surface tension of the composition. In some embodiments, the composition contains 15 to 40% by weight, particularly 20 to 38% by weight of component (c).
[0099] Examples of inert solvents that can be used as component (c) include water, alcohol solvents, ether solvents, amide solvents, ketone solvents, sulfoxide solvents, sulfone solvents, nitrile solvents, and organophosphorus solvents. Examples of alcohol solvents that can be used or used in combination with water (particularly with water) include methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and mixtures containing two or more of these. Additionally, preferred inert organic solvents that can be used for component (c) include dimethyl sulfoxide, dimethylimidazolinone, sulfolane, N-methylpyrrolidone, dimethylformamide, acetonitrile, acetone, 1,4-dioxane, 1,3-dioxolane, tetramethylurea, hexamethylphosphoramide, hexamethylphosphoric triamine, pyridine, propionitrile, butanone, cyclohexanone, tetrahydrofuran, tetrahydropyran, 2-methyltetrahydrofuran, ethylene glycol diacetate, cyclopentylmethyl ether, methyl ethyl ketone, ethyl acetate, γ-butyrolactone, and mixtures containing two or more of these. Preferably, dimethyl sulfoxide, N-methylpyrrolidone, dimethylformamide, dimethylimidazolinone, sulfolane, acetone, cyclopentylmethyl ether, methyl ethyl ketone, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, and mixtures containing two or more of these are preferred.
[0100] The composition preferably contains 0 to 2% by weight of component (d). When it is intended to cure the composition by heat or by using light (e.g., UV or visible light), the composition preferably contains 0.001 to 2% by weight, particularly 0.005 to 0.9% by weight of component (d).
[0101] Examples of suitable thermal initiators that can be used as component (d) include: 2,2'-azobis(2-methylpropionitrile) (AIBN), 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(2,4-dimethylpentanonitrile), 2,2'-azobis(2-methylbutanonitrile), 1,1'-azobis(cyclohexane-1-carboxylonitrile), 2,2'-azobis(4-methoxy-2,4-dimethylpentanonitrile), dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide, 1-[(1-cyano-1-methylethyl)azo]formamide, 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis(2-methylpropionamide) 2,2'-Azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-Azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, 2,2'-Azobis[N-(2-carboxyethyl)-2-methylpropane] hydrate, 2,2'-Azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane] hydrate Alkyl dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(1-imino-1-pyrrolidin-2-ethylpropane) dihydrochloride, 2,2'-azobis{2-methyl-N-[1,1-di(hydroxymethyl)-2-hydroxyethyl]propionamide} and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].
[0102] Examples of suitable photoinitiators that can be included as component (d) in the composition include aromatic ketones, acylphosphine compounds, aromatic onium salts, organic peroxides, thio compounds, hexaaryl biimidazole compounds, ketooxime esters, borate compounds, azadinium compounds, metallocene compounds, active ester compounds, compounds having carbon-halogen bonds, and alkylamine compounds. Preferred examples of aromatic ketones, acylphosphine oxide compounds, and thio compounds include compounds having a benzophenone backbone or a thioxanone backbone, described in “RADIATION CURING IN POLYMER SCIENCE AND TECHNOLOGY”, pp. 77-117 (1993). More preferred examples include α-thiobenzophenone compounds described in JP1972-6416B (JP-S47-6416B), JP1972-3981B (JP-S47-3981). Benzoin ether compounds described in B), α-substituted benzoin compounds described in JP1972-22326B (JP-S47-22326B), benzoin derivatives described in JP1972-23664B (JP-S47-23664B), aromatic phosphonates described in JP1982-30704A (JP-S57-30704A), dialkoxybenzophenones described in JP1985-26483B (JP-S60-26483B), benzoin ethers described in JP1985-26403B (JP-S60-26403B) and JP1987-81345A (JPS62-81345A), JP1989-34242B (JPH01-34242B), and the United States The following are listed: α-aminobenzophenone as described in patents 4,318,791A and EP0284561A1; p-bis(dimethylaminobenzoyl)benzene as described in JP1990-211452A (JP-H02-211452A); thiosubstituted aromatic ketones as described in JP1986-194062A (JPS61-194062A); acylphosphine sulfides as described in JP1990-9597B (JP-H02-9597B); acylphosphine as described in JP1990-9596B (JP-H02-9596B); thioxanthone as described in JP1988-61950B (JP-S63-61950B); and coumarin as described in JP1984-42864B (JP-S59-42864B). In addition, the photoinitiators described in JP2008-105379A and JP2009-114290A are also preferred.Alternatively, the photoinitiator described on pages 65-148 of "Ultraviolet Curing System" by Kato Kiyomi (Research Center Co., Ltd., published in 1989) can be used.
[0103] Particularly preferred photoinitiators include Norrish type II photoinitiators, which exhibit maximum absorption at wavelengths greater than 380 nm when measured at 23°C in one or more of the following solvents: water, ethanol, and toluene. Examples include xanthones, flavonoids, curcumin, porphyrins, anthraquinones, phenoxazines, camphorquinones, phenazines, acridines, phenothiazines, xanthonesones, thioxanthonesones, thioxanthones, acridine ketones, flavonoids, coumarins, fluorenones, quinoline, quinolones, naphthoquinones, quinolinones, arylmethanes, azo compounds, benzophenones, carotenoids, anthocyanins, phthalocyanines, dipyrrole methylene, squarine, stilbene, styryl, triazine, or anthocyanin-derived photoinitiators.
[0104] According to a third aspect of the present invention, a method for preparing a polymer film is provided, comprising curing a composition of the second aspect of the present invention.
[0105] Preferred embodiments of the polymer film and composition used in the method of the third aspect of the invention are as described herein with respect to the first and second aspects of the invention.
[0106] The composition can be cured by any suitable method to prepare the film of the first aspect of the invention, including thermal curing, photocuring, electron beam (EB) irradiation, gamma irradiation, and combinations thereof. Optionally, dual curing—defined as a combination of two of the above curing techniques—can be used. However, the composition is preferably cured by photocuring (e.g., by irradiating the composition with ultraviolet or visible light), thereby polymerizing the curable components present in the composition.
[0107] Preferably, the polymer membrane of the first aspect of the invention further comprises a porous support. For example, the composition of the second aspect of the invention may further comprise a porous support, and when the composition of the first aspect of the invention comprises a porous support, the method of the third aspect of the invention can be performed.
[0108] Porous supports can be used to provide mechanical strength to polymer membranes, which is especially useful when the polymer membrane is intended to be used as a cation exchange membrane (CEM) or a bipolar membrane (BPM).
[0109] Examples of porous carriers that can be used include woven and nonwoven synthetic fabrics and extruded membranes. Examples include wet-laid and dry-laid nonwoven materials, spunbond and meltblown fabrics, and nanofiber webs made from, for example, polyethylene, polypropylene, polyacrylonitrile, polyvinyl chloride, polyphenylene sulfide, polyester, polyamide, polyaryletherketone (e.g., polyetheretherketone) and their copolymers. Porous carriers can also be porous membranes, such as polysulfone, polyethersulfone, polyphenylene sulfone, polyphenylene sulfide, polyimide, polyetherimide, polyamide, polyamide-imide, polyacrylonitrile, polycarbonate, polyacrylate, cellulose acetate, polypropylene, poly(4-methyl-1-pentene), polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, and polychlorotrifluoroethylene membranes and their derivatives.
[0110] The average thickness of the porous carrier is preferably 10 to 800 μm, more preferably 15 to 300 μm, and particularly 20 to 150 μm.
[0111] Preferably, the porous support has a porosity of 30% to 95%. The porosity of the support can be measured using a porosimeter such as Porolux from IB-FT GmbH, Germany. TM 1000 was measured.
[0112] The porous support (if present) can be treated to alter its surface energy, for example, to a value higher than 45 mN / m, preferably higher than 55 mN / m. Suitable treatments include corona discharge treatment, plasma glow discharge treatment, flame treatment, ultraviolet irradiation treatment, or chemical treatment, for example, to improve the wettability of the porous support and its adhesion to polymer films.
[0113] Commercially available porous carriers are available from many sources, such as Freudenberg Filtration Technologies (Novatexx materials), Lydall Performance Materials, Celgard LLC, APorous Inc., SWM (Conwed Plastics, DelStar Technologies), Teijin, Hirose, Mitsubishi Paper Mills Ltd and Sefar AG.
[0114] Preferably, the carrier is a polymer carrier. More preferably, the carrier is a woven or nonwoven synthetic fabric or extruded film that does not contain covalently bonded ionic groups.
[0115] According to a fourth aspect of the invention, a bipolar membrane (BPM) is provided, comprising the polymer membrane of the first aspect of the invention.
[0116] Preferably, the polymer membrane is a cation exchange layer (CEL) of a cation exchange membrane (CEM) or a bipolar membrane (BPM), preferably obtained by a method comprising curing the composition of the second aspect of the invention and / or by a method of the third aspect of the invention. Preferably, the BPM further comprises an anion exchange layer (AEL).
[0117] Preferably, the polymer film of the first aspect of the present invention comprises groups of formula (A):
[0118]
[0119] Where M' + As defined above.
[0120] In formula (A), * indicates the position where the structural group is covalently attached to other groups in the polymer film (which may or may not be formula (A)).
[0121] In a preferred embodiment, the polymer film of the first aspect of the present invention is fluorine-free, for example, free of perfluorinated groups. This preference is for environmental reasons.
[0122] In a preferred method of the third aspect of the invention, the curable composition of the second aspect of the invention may preferably be continuously applied to a moving (porous) carrier by a manufacturing unit comprising a curable composition application station, one or more irradiation sources for curing the composition, a membrane collection station, and means for moving the carrier from the curable composition application station to the irradiation sources and the membrane collection station.
[0123] The curable composition application station may be located upstream of the irradiation source, and the irradiation source may be located upstream of the membrane collection station.
[0124] Examples of suitable coating techniques for applying the curable composition of the second aspect of the invention to a (porous) carrier include slot coating, glide coating, air knife coating, roll coating, screen printing, and dip coating. Depending on the technique used and the desired end specifications, excess coating may need to be removed from the substrate by, for example, roll-to-roll extrusion, roll-to-blade or blade-to-roll extrusion, blade-to-blade extrusion, or by removing the coating bar. Photocuring is preferably performed at wavelengths from 400 nm to 800 nm using 40 to 1500 mJ / cm². -2 The dosage is administered. In some cases, additional drying may be required, which can be performed at temperatures ranging from 40°C to 200°C.
[0125] The method of the third aspect of the invention can be used in several ways (including multi-pass and single-pass methods) to prepare, for example, polymer films of the first aspect of the invention and BPMs of the fourth aspect of the invention. For example, in a two-pass method, each layer of the BPM (e.g., CEL and AEL) can be produced in a separate step. In a first step of preparing the first layer, an optional pretreated porous carrier can be impregnated with a first curable composition. To ensure a thin and pinhole-free film, it is preferable to extrude to remove air after the coating step. The impregnated carrier can then be cured to produce a hard layer sufficient for processing in a coating machine, but still containing enough unreacted polymeric groups to ensure good adhesion to the second layer. In the second step, a method very similar to that of the first layer is used: the optional pretreated porous carrier can be impregnated with a second curable composition and laminated onto the first layer, then excess composition is extruded and cured.
[0126] In an alternative method for preparing BPM, a second layer can be coated onto the first layer, and then an optional pretreated porous carrier can be laminated onto one side of the second curable composition, thereby impregnating the porous carrier with the second curable composition. The resulting laminate can be extruded and cured to produce BPM.
[0127] In the two methods described above, the first curable composition or the second curable composition is as defined in the second aspect of the present invention.
[0128] In a more preferred single-pass method for preparing BPM, two optional pretreated porous carriers are unwound, and each carrier is impregnated with a curable composition (e.g., simultaneously or continuously), wherein one curable composition, as defined in the second aspect of the invention, yields a CEL, and the other curable composition contains at least one cationic curable monomer to provide an AEL. The two layers (the CEL from the composition of the second aspect of the invention and the AEL from the other curable composition) are then laminated together and extruded to remove air, and the resulting laminate is then cured to produce the final BPM.
[0129] The efficiency of BPM in the fourth aspect of the present invention can be improved by increasing the surface area between AEL and CEL, for example by physical treatment (roughening) or by other means.
[0130] In one embodiment, the BPM of the fourth aspect of the present invention may optionally include a catalyst, such as a metal salt, metal oxide, organometallic compound, monomer, polymer or copolymer or salt, preferably including the catalyst at the interface of the CEL and AEL of the BPM.
[0131] Suitable inorganic compounds or salts that can be used as catalysts include cations selected from, for example, Groups 1a to 4a (inclusive) of the periodic table, as well as lanthanides and actinides, such as thorium, zirconium, iron, lanthanum, cobalt, cadmium, manganese, cerium, molybdenum, nickel, copper, chromium, ruthenium, rhodium, tin, titanium, and indium, and combinations comprising two or more of the above. Suitable salts that can be used as catalysts include anions such as tetraborate, metaborate, silicate, metasilicate, tungstate, chlorate, phosphate, sulfate, chromate, hydroxyl, carbonate, molybdate, chloroplatinate, chloropaladite, orthovandate, tellurate, etc., or mixtures thereof.
[0132] Other examples of inorganic compounds or salts that can be used as catalysts include, but are not limited to, FeCl3, FeCl2, AlCl3, MgCl2, RuCl3, CrCl3, Fe(OH)3, Al2O3, NiO, Zr(HPO4)2, MoS2, graphene oxide, Fe-polyvinyl alcohol complexes, polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyethyleneimine (PEI), polyacrylic acid (PAA), copolymers of acrylic acid and maleic anhydride (PAAMA), and hyperbranched aliphatic polyesters, as well as combinations comprising two or more of the above.
[0133] When the polymer membrane of the first aspect of the invention is a CEM or CEL, it preferably has a very high density because it is made from the composition of the second aspect of the invention (where the molar fraction of component (a) relative to all curable components of the composition is greater than 0.25, for example, by ensuring that the composition contains a low amount of component (c) (e.g., 10 to 40 wt% of component (c)). Therefore, the present invention is capable of producing polymer membranes (e.g., CEM and BPM) with very high ion exchange capacity and thus high permeation selectivity (PS) and low resistivity (ER).
[0134] Preferably, the ER (for 0.5M NaCl) of the polymer membrane is less than 5 Ω·cm. 2 More preferably less than 2.5Ω·cm 2 .
[0135] Preferably, component (b) of the composition comprises compounds of formula (AM-B) and / or formula (III) as defined above (including the salts described above), as this can enable the polymer membranes (e.g., CEM and BPM) to have excellent pH stability in the range of 0 to 14.
[0136] Furthermore, the polymer membrane of the present invention, whether used as a CEM or as a CEL in a BPM, exhibits low resistance. Therefore, the polymer membrane and BPM of the present invention can be used in bipolar electrodialysis to provide high voltage at low current densities. Thus, when the BPM of the present invention is used in bipolar electrodialysis methods for producing acids and bases, they can provide low energy costs and / or high productivity.
[0137] In one embodiment, the polymer membrane of the first aspect of the present invention is preferably BPM or a membrane that can be converted into BPM by hydrolysis.
[0138] The anion exchange layer (AEL) of the BPM is preferably obtained by curing a composition containing a curable cationic compound (i.e., the "AEL composition"). Therefore, the AEL composition preferably contains a curable cationic compound.
[0139] Preferred curable cationic compounds comprise at least two olefinically unsaturated groups, for example, they are compounds of formula (IV):
[0140]
[0141] in:
[0142] L 1 It is an alkylene group or an alkenylene group;
[0143] R a R b R c and R d Each is independently an alkyl group or an aryl group, or
[0144] R a and R b , and / or R c and R d They can form rings together with the atoms they are attached to;
[0145] n1 and n2 each independently represent integers from 1 to 10; and
[0146] X1- and X2- represent anions independently.
[0147] L 1 Preferably, it is ethylidene (CH2CH2), propylidene (CH2CH2CH2), hexylidene (CH2CH2CH2CH2CH2CH2), or vinylidene (CH=CH).
[0148] When R a R b R c and R d When any one of them is an alkyl group, C is preferred.1-4 Alkyl groups, especially methyl groups.
[0149] When R a R b R c and R d When any one of them is an aryl group, C is preferred. 6-10 Aryl groups, especially phenyl groups.
[0150] When R a and R b , and / or R c and R d When the atoms to which they are attached form a ring, the ring is preferably a 5-membered or 6-membered ring.
[0151] From X1 and X2 - The anions represented are preferably halogens, especially Cl-. - .
[0152] Therefore, the AEL composition preferably contains the following components:
[0153] (a2) A cured cationic compound containing at least two olefinic unsaturated groups;
[0154] Option (b2) is a compound containing one and only one olefinic unsaturated group;
[0155] Optional (c2) solvent; and
[0156] Optional (d2) radical initiator.
[0157] Preferably, the AEL composition comprises at least one of components (b2), (c2) and (d2), more preferably at least two, and particularly all three.
[0158] Examples of compounds of formula (IV) include the following:
[0159]
[0160] Synthetic methods for compounds of formula (IV) can be found, for example, in EP3184558 and US2016 / 0001238.
[0161] The AEL composition preferably contains 30 to 80% by weight of component (a2), more preferably 40 to 70% by weight of component (a2).
[0162] Preferably, the AEL composition comprises:
[0163] (i) 30 to 80% by weight of the component (a2);
[0164] (ii) 0 to 60% by weight of component (b2); and
[0165] (iii) 10 to 40% by weight of the component (c2).
[0166] Component (b2) preferably contains aromatic groups.
[0167] Component (b2) preferably contains cationic groups.
[0168] Examples of compounds that can be used as component (b2) in AEL compositions include the following:
[0169]
[0170] The above compounds can be prepared as described, for example, in US2016177006.
[0171] Preferably, the molar ratio of component (a2) to component (b2) is 9:1 to 1:4.
[0172] The AEL composition preferably contains 0 to 45% by weight, more preferably 5 to 45% by weight, and most preferably 10 to 40% by weight of component (b2).
[0173] Preferably, component (c2) is an inert solvent. In other words, preferably, component (c2) does not react with any other component of the AEL composition.
[0174] Component (c2) of the AEL composition preferably includes water and, optionally, an organic solvent. Preferably, some or all of the organic solvent is water-miscible. Water can be used to dissolve compound (IV) and also to dissolve component (b2) (if present). The solvent can be used to reduce the viscosity and / or surface tension of the composition.
[0175] Examples of suitable solvents that can be used as component (c2) of an AEL composition include water, alcohol solvents, ether solvents, amide solvents, ketone solvents, sulfoxide solvents, sulfone solvents, nitrile solvents, organophosphorus solvents, and mixtures containing two or more of these. Examples of alcohol solvents that can be used as or for component (c2) (especially in combination with water) include methanol, ethanol, isopropanol, n-butanol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and mixtures containing two or more of these. Additionally, preferred inert organic solvents that can be used for component (c2) include dimethyl sulfoxide, dimethylimidazolinone, sulfolane, N-methylpyrrolidone, dimethylformamide, acetonitrile, acetone, 1,4-dioxane, 1,3-dioxolane, tetramethylurea, hexamethylphosphoramide, hexamethylphosphoric triamine, pyridine, propionitrile, butanone, cyclohexanone, tetrahydrofuran, tetrahydropyran, 2-methyltetrahydrofuran, ethylene glycol diacetate, cyclopentylmethyl ether, methyl ethyl ketone, ethyl acetate, γ-butyrolactone, and mixtures containing two or more of these. Preferably, dimethyl sulfoxide, N-methylpyrrolidone, dimethylformamide, dimethylimidazolinone, sulfolane, acetone, cyclopentylmethyl ether, methyl ethyl ketone, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, and mixtures containing two or more of these are preferred.
[0176] In some embodiments, the AEL composition comprises 10 to 40% by weight, more preferably 10 to 35% by weight, and most preferably 15 to 30% by weight of component (c2).
[0177] Examples of components (c2) to (d2) that may be included in the AEL composition for forming an AEL include those described above as components (c) and (d) for the CEL composition. However, component (c2) of the AEL composition is preferably aqueous.
[0178] Component (d2) is preferably or contains a thermal initiator, a photoinitiator, or a combination thereof. Most preferably, component (d) is or contains a photoinitiator.
[0179] Examples of suitable photoinitiators that can be used as component (d2) of an AEL composition include those described above with respect to the CEL compositions of the second aspect of the invention.
[0180] The AEL composition preferably contains 0.001 to 2% by weight of component (d2), more preferably 0.005 to 0.9% by weight.
[0181] The AEL and CEL compositions may optionally each further comprise a polymerization inhibitor independently. The polymerization inhibitor may be used to stabilize the composition during storage and use.
[0182] As polymerization inhibitors, well-known polymerization inhibitors can be used. Examples include phenolic compounds, hydroquinone compounds, certain amine compounds, thiol compounds, and nitrocellulose free radical compounds.
[0183] Examples of phenolic compounds include hindered phenols (phenols with a tert-butyl group at the ortho position, and representative examples include 2,6-di-tert-butyl-4-methylphenol) and bisphenols. Specific examples of hydroquinone compounds include monomethyl ether hydroquinone. Specific examples of amine compounds include N-nitroso-N-phenylhydroxylamine and N,N-diethylhydroxylamine. Specific examples of nitroacyl radical compounds include 4-hydroxyTEMPO (4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxy radical).
[0184] The AEL composition and the CEL composition may optionally each independently further comprise two or more polymerization inhibitors.
[0185] When the CEL composition or AEL composition contains a polymerization inhibitor, its content is preferably 0.01 to 5% by weight, more preferably 0.01 to 1% by weight, and even more preferably 0.01 to 0.5% by weight, relative to the total weight of the relevant composition.
[0186] The AEL composition and the CEL composition may optionally each further comprise, independently, a surfactant, a polymer dispersant, and / or a crater inhibitor.
[0187] To adjust the film physical properties of the AEL composition and / or CEL composition, various polymer compounds may be included. Suitable polymer compounds include acrylic polymers, polyurethane resins, polyamide resins, polyester resins, epoxy resins, phenolic resins, polycarbonate resins, polyvinyl butyral resins, polyvinyl formal resins, shellac, vinyl resins, acrylic resins, rubber-based resins, waxes, and natural resins, as well as combinations of two or more of the above.
[0188] The AEL and CEL compositions may optionally, independently, further comprise surfactants, such as nonionic surfactants, cationic surfactants, or organofluorine surfactants. Specific examples of surfactants include anionic surfactants (e.g., alkylbenzene sulfonates, alkylnaphthalene sulfonates, higher fatty acid salts, sulfonates of higher fatty acid esters, sulfates of higher alcohol ethers, sulfonates of higher alcohol ethers, alkyl carboxylates and alkyl phosphates of higher alkyl sulfonamides) and nonionic surfactants (e.g., poly(ethylene oxide) alkyl ethers, poly(ethylene oxide) alkylphenyl ethers, poly(ethylene oxide) fatty acid esters, sorbitan fatty acid esters, ethylene oxide adducts of acetylenic glycols, ethylene oxide adducts of glycerols, and polyoxyethylene sorbitan fatty acid esters). Other suitable examples of surfactants include amphoteric surfactants (e.g., alkyl betaines and amide betaines), organosilicon surfactants, and fluorinated surfactants. Surfactants may suitably be selected from surfactants known in the art or derivatives thereof.
[0189] The AEL composition and the CEL composition may optionally each further comprise a polymer dispersant independently.
[0190] Specific examples of polymer dispersants include polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl methyl ether, polyethylene oxide, polyethylene glycol, polypropylene glycol, and polyacrylamide. Among these, polyvinylpyrrolidone is preferred.
[0191] The AEL composition and CEL composition may optionally each independently further comprise an anti-cratering agent (sometimes called a surface conditioner), a leveling agent, or a slip agent to prevent non-uniformity of the CEM / CEL or AEL surface, examples of which include organically modified polysiloxanes (mixtures of polyether siloxanes and polyethers), polyether-modified polysiloxane copolymers, and silicone-modified copolymers.
[0192] Examples of commercially available surfactants that can be included in AEL compositions and / or CEL compositions include Tego Glide manufactured by Evonikindustries GmbH. TM 432. Tego Glide TM 110. Tego Glide TM 130. TegoGlide TM 406. Tego Glide TM 410. Tego Glide TM 411. Tego Glide TM 415. Tego Glide TM 420. Tego Glide TM 435. Tego Glide TM 440. Tego Glide TM 450. Tego Glide TM 482. Tego Glide TM A115, Tego Glide TM B1484 and Tego Glide TM ZG400 (both are product names).
[0193] The AEL composition and the CEL composition preferably each independently contain 0 to 10% by weight, more preferably 0 to 5% by weight, and especially 1 to 2% by weight of an anti-cracking agent (relative to the total weight of the relevant composition).
[0194] As described above, in a preferred embodiment, the BPM of the fourth aspect of the invention comprises a catalyst. In one embodiment, the AEL composition and / or CEL composition further comprises a catalyst. The catalyst may also be applied to the AEL (e.g., prior to applying the CEL composition thereon) as a post-treatment step using methods such as (but not limited to) impregnation, air knife coating, micro-roll coating, spraying, chemical (vapor) deposition, or physical (vapor) deposition. Examples of suitable catalysts are described above.
[0195] When the AEL composition or CEL composition contains a catalyst, the amount of catalyst is preferably up to 5% by weight, for example, from 0.001% by weight to 1% by weight, relative to the weight of the relevant composition.
[0196] The BPM of the fourth aspect of this invention can be prepared by a method comprising the following steps:
[0197] (i) Applying the AEL composition to a carrier;
[0198] (ii) Curing the AEL composition at least partially to form an anion exchange layer (AEL);
[0199] (iii) Applying the CEL composition to the AEL; and
[0200] (iv) Curing the CEL composition to form a cation exchange layer (CEL) on the AEL.
[0201] In step (ii), preferably, the AEL composition is photocured, for example, using ultraviolet light. Therefore, preferably, component (d2) of the AEL composition is or contains a photoinitiator.
[0202] In step (ii), preferably, the AEL composition is cured to such an extent that the resulting AEL can be processed in a curable composition application station while still containing unreacted olefinic unsaturated groups that can be crosslinked to one or more components of the CEL composition.
[0203] In step (iv), the CEL composition is preferably thermosetting. Therefore, preferably, component (d) of the CEL composition is or contains a thermal initiator.
[0204] The suitable temperature for curing the CEL composition is 50 to 120°C, more preferably 50 to 100°C, and particularly 60 to 85°C.
[0205] Thermosetting of CEL compositions typically takes anywhere from one minute to several hours.
[0206] Optionally, the CEL composition may be cured when it further contains a porous carrier sandwiched between transparent foils to prevent component (c) (if present) from evaporating.
[0207] The CEL and AEL compositions are preferably applied in a continuous manner, preferably by a manufacturing unit, in steps (i) and (iii), the manufacturing unit comprising a composition application station, one or more curing stations including an irradiation source (when the composition is photocurable), one or more curing stations including one or more heat sources (when the composition is thermocurable), a bipolar film collection station, and means for moving a carrier from the composition application station to the curing station and the bipolar film collection station.
[0208] The composition application station may be located upstream of the curing station, and the curing station may be located upstream of the bipolar membrane collection station.
[0209] Examples of application techniques include slot coating, glide coating, air knife coating, roll coating, screen printing, and dip coating. Depending on the technique used and the required end specifications, excess composition may need to be removed from the porous carrier by, for example, roll-to-roll extrusion, roll-to-blade or blade-to-roll extrusion, blade-to-blade extrusion, or removal using a coating bar.
[0210] UV or visible light curing is preferably performed at wavelengths from 100 nm to 800 nm, typically using 40 to 1500 mJ / cm². 2 The light dose is applied. Thermocuring is preferably carried out at a temperature of 20°C to 100°C for a time of, for example, 0.01 hours to 24 hours.
[0211] The performance of the BPM in the fourth aspect of the invention is characterized by an intensity vs. voltage curve. For measuring this curve, a six-chamber cell is preferably used. The first electrode chamber preferably contains a platinum plate as a cathode and is separated from the second chamber by a CEM (CMX from Astom). The electrode chamber is preferably filled with 0.5 M Na₂SO₄. A reference BPM (from Fumatech) is preferably present between the second and third chambers. Both the second and third chambers preferably contain a 0.5 M NaCl solution. The BPM to be analyzed is placed between the third and fourth chambers. The same reference BPM (from Fumatech) is placed between the fourth and fifth chambers, and a CEM (CMX from Astom) is placed between the fifth and sixth chambers. Preferably, the fourth and fifth chambers are also filled with a 0.5 M NaCl solution. The sixth chamber preferably contains a platinum plate as an anode and is also an electrode chamber, containing 0.5 M Na₂SO₄.
[0212] By using the aforementioned six-chamber battery cell, a 0.5M NaCl and Na2SO4 solution can be discharged at a temperature of 25°C and a current of 600A / m. 2 The fluid is pumped through the corresponding chamber at the applied current density. The bipolar voltage can be measured using Harber-Luggin capillaries placed on each side of the BPM to be analyzed.
[0213] The CEM and BPM containing a cation exchange layer (CEL) of the present invention exhibit good pH stability, high permeability selectivity, and low resistivity. Therefore, the CEM and BPM of the present invention can be used in bipolar electrodialysis to provide high voltage at low current densities. Thus, when the BPM of the present invention is used in bipolar electrodialysis methods for producing acids and bases, they can provide low energy costs and / or high productivity. Example
[0214] In the following non-limiting embodiments, all parts and percentages are by weight unless otherwise specified.
[0215] Table 1: Ingredients
[0216]
[0217]
[0218] The lithium content of the prepared compound of formula (I) was quantified using inductively coupled plasma atomic emission spectrometry (ICP-OES). Thermo iCAP from Thermo Fisher Scientific was used. TM ICP-OES analysis was performed using the PRO XP ICP-OES instrument. A concentric nebulizer was used in conjunction with a cyclone chamber. Approximately 50 mg of each analyte was dissolved in a 50 cm³ solution. 3 The dissolved compound was diluted 100-fold in Milli-Q water and acidified with 0.5% concentrated nitric acid containing yttrium as an internal standard. All samples were prepared and measured in duplicate. Results are expressed as g Li / kg monomer.
[0219] The structure of compound (I) was obtained using a Magritek Spincolve 60-carbon (60 MHz, 4 scans) NMR spectrometer. 1 ¹H-NMR confirmed the results. Analytical samples were prepared by dissolving 5% by weight of each compound of formula (I) in DMSO-d6.
[0220] Examples of the structures of compounds of formula (I):
[0221]
[0222] The purity of compound (I) was determined by HPLC-MS. A Waters ACQUITY UPLC system with 2D technology was used. This UPLC is equipped with two pumps (BSM and QSM), an FTN sample manager, a column manager, and a PDA detector (192 to 400 nm). The HPLC was equipped with a Waters Xbridge C8 5 μm 2.1*150 mm column operating at 45 °C. Additionally, the instrument was equipped with a Waters Q-TOF premier mass spectrometer with ESI and ESCi ionization options. Chromatograms were collected using dual detection mode. The PDA detector collected the signal at 245 nm. The mass detector was set to negative mode to detect anionic molecules. Samples containing compound (I) were prepared as follows: 5 mg of compound (I) was dissolved in 50 mL of Milli-Q water. The resulting solution was diluted 10-fold with Milli-Q water, and 10 μL was injected into the HPLC-MS instrument for analysis.
[0223] Table 2 shows a typical method for eluting samples of compound (I) shown in Table 3. Table 3 provides an overview of retention times and molecular weights recorded for material identification.
[0224] Table 2: HPLC methods
[0225]
[0226] Table 3: Identification of materials and impurities in the examples
[0227]
[0228] *Retention time is indicative. Small variations in retention time were observed between samples, depending on sample purity and other factors. Cl-SS and Cl-DVBS are converted to their sulfonic acids upon dissolution in water.
[0229] The solubility of compounds of formula (I) was determined visually or by ultraviolet spectroscopy. For each compound of formula (I), three solutions were prepared at 40 °C: a 30 wt% solution, a 60 wt% solution, and a 70 wt% solution. All three solutions contained 500 ppm 4OH-TEMPO to prevent premature polymerization. The solutions were stored overnight in a 40 °C water bath and centrifuged before examination. The solubility was determined using quartz cuvettes with a 1 mm path length from Agilent Technologies' Cary TM The ultraviolet spectrum was recorded in a UV-Vis spectrophotometer.
[0230]
[0231] Table 4: Solubility of several compounds of formula (I) and comparative compound (DVBS-Na) in water
[0232]
[0233] In experiments conducted separately from those shown in Table 4, for comparison, the highest solubility obtained by combining lithium styrene sulfonate (LiSS) and DVBS-Na was 55% by weight, while compositions with a solid content exceeding 70% by weight were achieved when such monomers (e.g., LiSS and NaSS) were combined with compounds of formula (I).
[0234] The ER (Ω·cm) of the polymer membrane prepared in the examples 2 The measurement was performed using the method described by Dlugolecki et al. in J. of Membrane Science, 319 (2008), pp. 217-218, with the following modifications:
[0235] • The auxiliary membranes are CMX and AMX from Tokuyama Soda in Japan;
[0236] • The capillary and Ag / AgCl reference electrode (Metrohm 6.0750.100 type) contain 3M KCl;
[0237] • The calibration liquid and the liquids in compartments 2, 3, 4 and 5 are 0.5M NaCl solutions at 25°C;
[0238] • The effective polymer film area is 9.62 cm². 2 ;
[0239] • The distance between capillaries is 5.0 mm;
[0240] • The measured temperature is 25℃;
[0241] • All compartments are driven by a Cole Parmer Masterflex console (77521-47) with an Easy-Load Type II 77200-62 gear pump;
[0242] • The flow rate per stream was controlled at 475 ml / min using a Porter Instrument flow meter (150AV-B250-4RVS model) and a Cole Parmer flow meter (G-30217-90 model); and
[0243] • Before measurement, equilibrate the polymer film sample in a 0.5M NaCl solution at room temperature for at least 1 hour.
[0244] Preferably, the ER (for 0.5M NaCl) is less than 5 Ω·cm.2 More preferably, below 2.5Ω·cm 2 .
[0245] Measurement of permeation selectivity (PS)
[0246] The permeation selectivity PS (%) was measured as follows, which is the selectivity for ions with opposite charges to those prepared in the examples. The polymer membrane to be analyzed was placed in a two-compartment system. One compartment was filled with 0.05 M NaOH solution, and the other compartment was filled with 0.5 M NaOH solution.
[0247] set up:
[0248] • The capillary and Ag / AgCl reference electrode (Metrohm 6.0750.100 type) contain 3M KCl;
[0249] • The effective polymer film area is 9.62 cm². 2 ;
[0250] The distance between the capillaries is approximately 15 mm;
[0251] • The measured temperature was 21.0 ± 0.2℃;
[0252] • Both compartments are driven by a Cole Parmer Masterflex console (77521-47) with an easy-load Type II 77200-62 gear pump;
[0253] • The flow constant was controlled at 500 ml / min using a Porter Instrument flow meter (150AV-B250-4RVS type) and a Cole Parmer flow meter (G-30217-90 type);
[0254] • Before measurement, equilibrate the polymer membrane sample in 0.5M NaOH solution for 1 hour. Read the voltage from a standard VOM (multimeter) after 20 minutes.
[0255] Preferably, the PS content of NaOH is at least 50%.
[0256] pH stability
[0257] Stability under acidic and / or alkaline conditions is preferred because it broadens the range of applications for which the polymer membrane can be used. Stability is typically tested by immersing a sample of the polymer membrane to be evaluated in 4M HCl or NaOH at 80°C for 7 days. After this treatment, the polymer membrane should retain at least 80% of its original selectivity to be considered stable.
[0258] Extraction Analysis
[0259] To analyze the degree of polymerization of the polymer membrane and to indicate the presence of the material to be protected within the polymer membrane, purified water (in 50 mL of purified water at a concentration of 10 cm⁻¹) was used. 2 The polymer membrane sample was extracted, and the extract was then analyzed using the HPLC-MS method described above.
[0260] Preparation of Formula (I) and Comparative Compounds
[0261] Synthesis of starting materials
[0262] Cl-SS
[0263]
[0264] In a double-walled reactor actively cooled to 5°C, thionyl chloride (109 mL, 178.46 g, 1.5 mol, 3 molar equivalent) was added dropwise to a DMF (300 mL) solution of lithium 4-vinylbenzenesulfonate (95.08 g, 0.500 mol, 1 molar equivalent) and 4OH-TEMPO (50 mg, 500 ppm). After the addition was complete, the solution was slowly heated to room temperature and stirred for 16 hours. The reaction mixture was then poured into 1 L of cold 1M KCl in a separatory funnel. The bottom layer was removed and dissolved in 500 mL of diethyl ether. The solution was washed with 1M KCl- solution (300 mL). The organic layer was dried over sodium sulfate, filtered, and concentrated under vacuum to obtain a yellow oil. The crude product was ready for use in the next step without further purification. Typical yield was 89.5 g (88%). HPLC-MS purity >98%; 1 H-NMR: <2% DMF by weight, 0% diethyl ether.
[0265] Cl-DVBS
[0266]
[0267] In a double-walled reactor actively cooled to 5°C, thionyl chloride (75 mL, 123.1 g, 1.034 mol, 3 molar equivalent) was added dropwise to a solution of sodium divinylbenzenesulfonate (80 g, 0.345 mol, 1 molar equivalent) and 4OH-TEMPO (50 mg, 500 ppm) in DMF (300 mL). After the addition was complete, the solution was slowly heated to room temperature and stirred for 16 hours. The reaction mixture was then poured into 1 L of cold 1M KCl in a separatory funnel. The bottom layer was removed and dissolved in 500 mL of diethyl ether. The solution was washed with 1M KCl solution (300 mL). The organic layer was dried over sodium sulfate, filtered, and concentrated under vacuum to obtain a yellow oil. The crude product was ready for use in the next step without further purification. Typical yield was 62 g (79%). HPLC-MS purity >98%; 1 H-NMR: <2% DMF by weight, 0% diethyl ether.
[0268] NH2-SS
[0269]
[0270] In a double-walled reactor actively cooled to 5°C, thionyl chloride (109 mL, 178.46 g, 1.5 mol, 3 molar equivalent) was added dropwise to a DMF (300 mL) solution of lithium 4-vinylbenzenesulfonate (95.08 g, 0.500 mol, 1 molar equivalent) and 4OH-TEMPO (50 mg, 500 ppm). After the addition was complete, the solution was slowly heated to room temperature and stirred for 16 hours. The reaction mixture was then poured into 1 L of cold 1M KCl in a separatory funnel. The bottom layer was removed, and the mixture was added dropwise in a 25% ammonium hydroxide aqueous solution (250 mL, 3.67 mol, 15 molar equivalent) and 4OH-TEMPO (50 mg, 500 ppm) in a double-walled reactor actively cooled to 5°C. After the addition was complete, the solution was stirred for 1 hour. The solution was then heated to room temperature and stirred for 1 hour. The reaction mixture was then cooled back to 5°C, the product was filtered off, and washed with 50 mL of cold water. The product was vacuum-dried overnight at 30°C and used without further purification. Typical yield was 66.8 g (73%). HPLC-MS purity >95%.
[0271] Synthesis of compound (I):
[0272] Example 1-XL-D
[0273]
[0274] Prior to synthesis, methanesulfonamide was dried overnight in a vacuum oven (30°C, vacuum). LiH (1.53 g, 0.192 mol, 2.2 mol equivalent) as solid was immediately added to a THF (100 mL) solution of dried methanesulfonamide (8.32 g, 0.087 mol, 1 mol equivalent) and 4OH-TEMPO (30 mg, 500 ppm). The reaction mixture was stirred at room temperature for 30 minutes. Then, a THF (50 mL) solution of Cl-DVBS (20 g, 0.087 mol, 1 mol equivalent) was added to the reaction mixture. After addition, the reaction mixture was heated to 60°C (water bath temperature). Two days later, the reaction mixture was filtered with Celite to remove excess LiH. The filtrate was concentrated under vacuum to obtain a pale yellow foam. The resulting foam was dissolved in 500 mL of ethyl acetate. Celite was added, and the resulting slurry was stirred for 5 minutes. The Celite was then filtered off, and the mixture was washed with 100 mL of ethyl acetate. This Celite procedure was then repeated. The solvent was then evaporated under vacuum, and the resulting white foam was washed overnight with 500 mL of diethyl ether. The resulting white powder was filtered off and dried in a vacuum oven at 30 °C for 16 h, yielding a hygroscopic white solid. A typical yield was 15.5 g (60%). HPLC-MS purity >95%. 1 H-NMR: <3% by weight residual solvent; 2% by weight divinylbenzenesulfonate; ICP-OES: 24-30 g Li / kg product.
[0275] Example 2-XL-B
[0276]
[0277] Prior to synthesis, benzenesulfonamide was dried overnight in a vacuum oven (30°C, vacuum). LiH (1.06 g, 0.134 mol, 2.2 mol equivalent) as solid was immediately added to a THF (100 mL) solution of dried benzenesulfonamide (11.12 g, 0.061 mol, 1 mol equivalent) and 4OH-TEMPO (30 mg, 500 ppm). The reaction mixture was stirred at room temperature for 30 minutes. Then, a THF (50 mL) solution of Cl-SS (12.3 g, 0.061 mol, 1 mol equivalent) was added to the reaction mixture. After addition, the reaction mixture was heated to 60°C (water bath temperature). Two days later, the reaction mixture was filtered through Celite to remove excess LiH. Celite was added, and the resulting slurry was stirred for 5 minutes. Then, the Celite was filtered off, and the mixture was washed with 100 mL of ethyl acetate. The solvent was then evaporated under vacuum, and the resulting white foam was washed overnight with 500 mL of diethyl ether. The resulting white powder was filtered off and dried in a vacuum oven at 30°C for 16 h to produce a white solid. The typical yield was 11 g (51%). HPLC-MS purity >94%. 1 H-NMR: <1% by weight residual solvent; <5% by weight styrene sulfonate or styrene sulfonamide; ICP-OES: 21-26 g Li / kg product.
[0278] Example 3-XL-2
[0279]
[0280] Prior to synthesis, styrene sulfonamide was dried overnight in a vacuum oven (30°C, vacuum). LiH (1.50 g, 0.189 mol, 4.2 mol equivalent) as solid was immediately added to a THF (100 mL) solution of dried styrene sulfonamide (16.90 g, 0.092 mol, 2.05 mol equivalent) and 4OH-TEMPO (30 mg, 500 ppm). The reaction mixture was stirred at room temperature for 30 minutes. Then, a THF (50 mL) solution of 1,3-benzenedisulfonyl chloride (12.38 g, 0.045 mol, 1 mol equivalent) was added to the reaction mixture. After addition, the reaction mixture was heated to 60°C (water bath temperature). After 2 days, the reaction mixture was filtered with Celite to remove excess LiH. The filtrate was concentrated under vacuum to obtain a pale yellow foam. The resulting foam was dissolved in 500 mL of ethyl acetate. Celite was added, and the resulting slurry was stirred for 5 minutes. The Celite was then filtered off and the sample was washed with 100 mL of ethyl acetate. This Celite procedure was then repeated. The solvent was then evaporated under vacuum, and the resulting white foam was washed overnight with 500 mL of diethyl ether. The resulting white powder was filtered off and dried in a vacuum oven at 30 °C for 16 h to produce a hygroscopic white solid. A typical yield was 14.5 g (54%). HPLC-MS purity >96%. 1 H-NMR: <2 wt% residual solvent; <2 wt% styrene sulfonamide; ICP-OES: 35-40 g Li / kg product.
[0281] Example 4-XL-SAS
[0282] Step 1
[0283]
[0284] LiH was added to a THF solution of bisbenzylsulfonamide. The reaction mixture was stirred for 15 minutes. Vinylbenzenesulfonyl chloride was then immediately added, and the reaction mixture was heated to 50°C. After 20 hours at 50°C, the reaction mixture was cooled to room temperature, filtered, and the residue was washed with THF. The filtrate was concentrated under vacuum. The resulting solid was stirred in diethyl ether and filtered again. The filtrate was concentrated under vacuum and purified by column chromatography.
[0285] Step 2
[0286]
[0287] Benzyl-protected LiBVBSAS was dissolved in DCM and TFA and stirred overnight at room temperature. The product was filtered off, dried under vacuum, and separated as a white solid. The typical yield of the two steps was 45%, with HPLC-MS purity >96%.1 H-NMR: <2 wt% residual solvent; <2 wt% styrene sulfonamide; ICP-OES: 35-40 g Li / kg product.
[0288] Preparation of component (b)
[0289] The structures of MM-Tf, MM-A, MM-P, and MM-M (as described above) are shown below.
[0290]
[0291] Compounds MM-Tf, MM-A, MM-P, and MM-M were synthesized according to the following general scheme and procedure:
[0292]
[0293] General Procedure
[0294] Prior to synthesis, the corresponding sulfonamide was dried overnight in a vacuum oven at 30°C. LiH (0.300 mol, 3 mol equivalents) as solid was immediately added to a THF (100 mL) solution of the dried sulfonamide (0.100 mol, 1 mol equivalent) and 4OH-TEMPO (30 mg, 500 ppm). The reaction mixture was stirred at room temperature for 30 minutes. Then, a THF (50 mL) solution of vinylbenzylsulfonyl chloride (0.100 mol, 1 mol equivalent) was added, and the reaction mixture was heated to 60°C (water bath temperature) and maintained for 16 hours. The resulting solution was filtered through Celite, and the resulting foam was dissolved in 500 mL of ethyl acetate. Celite was added, and the resulting slurry was stirred for 5 minutes. The Celite was then filtered off, and the mixture was washed with 100 mL of ethyl acetate. The solvent was then evaporated under vacuum, and the resulting white foam was pulverized overnight with 500 mL of diethyl ether. The resulting compound of formula (b) was collected by filtration and separated into a white hygroscopic powder. Table 5 below provides data on yield and purity.
[0295] Table 5: Compounds of Formula (b) and Comparative Compounds
[0296] methyl 80% >94% <1% <4% 26-30g / kg Phenyl 79% >96% <1% <2% 23-28g / kg Trifluoromethyl 70% 81% 17% amino 63% >92% <1% <6% 26-40g / kg
[0297] Composition Examples (Ex) 1 to 11, Comparative Examples CEx1 to CEx5, and Polymer Film
[0298] Table 6 below describes the compositions of Examples 1 to 11 and Comparative Examples CEx1 to CEx5 of the second aspect of the present invention. Each composition was polymerized to form a polymer film with a thickness of 100 μm by coating the compositions described in Table 6 below onto a PP / PE support for reinforcement using a 100 μm Meyer rod. The resistivity (ER) of the resulting polymer film was measured using 0.5 NNaCl, and the permeability selectivity (PS) was measured as described above; the results are shown in Table 7 below. The pH of the resulting polymer film was measured using the method described above, and the results are also shown in Table 7 below.
[0299] Table 6: Compositions
[0300]
[0301] The Na-AMPS amounts in the table are based on Na-AMPS being 100% solids. The water content of Na-AMPS (provided by the supplier) is included in the amount of component (c).
[0302] M represents moles per kg.
[0303] Table 7: ER, PS and pH stability of polymer membranes
[0304]
[0305] nm indicates unmeasured.
[0306] Extraction Analysis
[0307] The results of the above extraction and analysis are shown in Table 8 below.
[0308] Table 8: Extraction Results
[0309]
[0310] Preparation of AEL
[0311] An AEL composition was prepared comprising N,N,N',N'-tetramethyldiaminopropane, 1,4-bis[(4-vinylphenyl)methyl]-,chloride (46.1 wt%), 4-vinylbenzyltrimethylammonium chloride (23 wt%), water (28 wt%), 4-hydroxyTEMPO (2 wt%), and Omnirad. TM 1173 (0.9% by weight). The AEL composition was coated onto a PE carrier and cured by UV to obtain AEL.
[0312] Prepare a CEL and apply it to an AEL to generate a BPM.
[0313] Prepare the CEL composition described in Table 7 (Example 9 and Comparative Example CEx4), coat it onto the AEL prepared as described above, then place a second PE carrier on the CEL composition layer, wipe off the excess CEL composition, and cure the CEL composition with UV light to obtain BPM.
[0314] The electrochemical performance and bipolar properties of the BPM thus prepared were compared with a reference bipolar film (Fumasep from Fumatech) using a so-called current-voltage characteristic (IU curve), where the current density is measured as a function of the applied voltage. Typically, a given current density (i.e., 600 mA / cm²) is generated. 2 The required low voltage (U) indicates that one or both of AEL and CEL, as well as BPM, have low ionic resistance. In the case of CEL, low ionic resistance results in a more energy-efficient membrane. The results for Example 9 and Comparative Example CEx4 are shown in Table 9 below.
[0315] Table 9: Voltage U of CEL's ER and BPM at 600mA / cm2
[0316]
Claims
1. A polymer film obtainable by curing a composition comprising: (a) 60 to 70% by weight of compound (I): Equation (I) in: R' is vinyl, epoxy, or C. 1-3 alkylene mercapto; The value of n is 1 or 2; The value of m is 1, 2, or 3; M' + It is a cation; in: (i) When both m and n are 1, X is a vinylphenyl or formula (II): Equation (II) In equation (II): R'' is vinyl, epoxy, or C. 1-3 alkylene mercapto; M'' + It is a cation; and In equation (II), the value of n is 1 or 2; (ii) When the value of m is 2 or 3, then X is C. 1-6 Alkylene, C 6-18 Aryl or N(R''') (3-m) Each R''' is independently H or C 1-4 Alkyl; and (iii) When the value of m is 1 and the value of n shown in equation (I) is 2, then X is equation (II) or C. 1-6 Alkyl, C 6-18 Aryl or N(R''')2, where each R''' is independently H or C. 1-4 Alkyl groups; and (b) 5 to 40% by weight of compounds containing a disulfonamide group and one and only one polymerizable group; Wherein, the molar fraction of the compound of formula (I) relative to all curable compounds in the composition is greater than 0.30; and The polymer film therein does not contain perfluorinated groups.
2. The polymer film according to claim 1, wherein, In Equation (I), the value of n is 1 and the value of m is 2.
3. The polymer film according to claim 1, wherein, M' + and M'' + Selected from H + Li + Na + K + Or NL4 + Each L is independently H or C 1-3 alkyl.
4. The polymer film of claim 1, wherein one and only one polymerizable group is a vinyl group.
5. The polymer film of claim 1, wherein component (b) comprises a compound of formula (III): Equation (III) in R is a C1-C4 alkyl group, NH2, or C6-C. 12 Aryl; and M + It is H + Li + Na + K + NL4 + , where L is H or C1-C3 alkyl.
6. A composition comprising the following components: (a) 60 to 70% by weight of the compound of formula (I); (b) 5 to 40% by weight of compounds containing a bissulfonylimide group and one and only one polymerizable group. in, The compound of formula (I) is as defined in claim 1.
7. The composition of claim 6, further comprising: (c) Solvent; and (d) Free radical initiators.
8. The composition of claim 6 or 7, further comprising: (c) 10 to 40% by weight of component (c); and (d) 0 to 10% by weight of the component (d).
9. The composition of claim 6 or 7, wherein component (b) comprises a compound of formula (III): Equation (III) in R is a C1-C4 alkyl group, NH2, or C6-C. 12 Aryl; and M + It is H + Li + Na + K + NL4 + , where L is H or C1-C3 alkyl.
10. A method for preparing a polymer film, comprising curing the composition of claim 6 or 7.
11. The polymer membrane according to claim 1, wherein it is a cation exchange membrane.
12. A bipolar membrane comprising the polymer membrane of claim 1.
13. The polymer membrane of claim 11 or the bipolar membrane of claim 12, further comprising a porous support.
14. Use of the polymer membrane of claim 11 for treating polar liquids, for generating hydrogen, or for generating electricity.
15. The bipolar membrane of claim 12 is used for the production of acids and bases, for the separation and treatment of organic acids, or for the generation of electricity.
Citation Information
Patent Citations
Alpha-aminoacetophenones as photo initiators
EP0284561A2
Composition for forming polymeric membrane, process for producing same, polymeric membrane, separation membrane module, and ion exchange device
EP3184558A1
JP1972003981B1
JP1972006416B1
JP1972022326B1